"A ROSE, by any other name"…: relationship typology and performance measurement in supply chains. Issue 4 (2014) - ,; ,; ,
Abstract : Purpose – The aim of this paper is to develop a comprehensive framework of supply chain performance that includes relationship, operational, strategic and economic performance measures.Design/methodology/approach – The literature regarding inter‐organizational performance including: supply chain management, logistics and marketing performance measures is reviewed. A synthesis of the review provides the foundation for developing a comprehensive model of supply chain management performance.Findings – The review and synthesis finds that supply chain performance focuses primarily on operational and economic performance measures while paying less attention to relational and strategic performance measures. The comprehensive framework identifies four major categories of supply chain performance measures: relational; operational; strategic; and economic – hence the name ROSE.Originality/value – This comprehensive framework identifies four types of supply chain measures that can be used as a guiding framework by both academics and practitioners. The paper also offers directions for future work in the form of propositions.